Exposure to pesticide mixtures and DNA damage among rice field workers (2016)
This study describes the use of pesticides mixtures and their potential association with comet assay results in 223 rice field workers in Colombia. Thirty-one pesticides were quantified in blood, serum, and urine (15 organochlorines, 10 organophosphorus, 5 carbamates, and ethylenethiourea), and the comet assay was performed. Twenty-four (77.42%) pesticides were present in the workers. The use of the maximum-likelihood factor analysis identified 8 different mixtures. Afterwards, robust regressions were used to explore associations between the factors identified and the comet assay. Two groups of mixtures-?-benzene hexachloride (?-BHC), hexachlorobenzene (HCB), and ?-BHC (?: 1.21, 95% confidence interval [CI]: 0.33-2.10) and pirimiphos-methyl, malathion, bromophos-methyl, and bromophos-ethyl (?: 11.97, 95% CI: 2.34-21.60)-were associated with a higher percentage of DNA damage and comet tail length, respectively. The findings suggest that exposure to pesticides varies greatly among rice field workers. © 2016 Taylor and Francis.